Business evolution or revolution? Mail-order pharmacies in Germany. (1st September 2004) - Gersch, Martin
It is an interesting detail of the present reform of national public health service in Germany that mail-order and internet pharmacies will be founded in future as new (e-commerce) business models. Main points of conceivable business systems can be characterised as well as critical success factors. No potential participant can ever have all the necessary resources and competences to implement a competitive business system without external support. This is why cooperation seems to be a useful tool for competence management. The Resource-based View will serve as theoretical background for analysis. The required and available competences of conceivable players can be identified. Features of resources can be described that recommend special types of cooperation with the intention of establishing and operate a business system. Especially German and international pharmaceutical wholesalers can be identified as conceivable "parents" of mail-order pharmacies in the future.